SPEAK UP®: DEVELOPING INDONESIAN EFL LEARNERS’ VOCABULARY AND IMPROVING THEIR SPEAKING SKILLS - Ima Normalia Kusmayanti (University of Kuningan, 2025)
Research indicates that incorporating educational games can significantly enhance second or foreign language learning. This study examines the effectiveness of the board game Speak Up® in improving English vocabulary and speaking skills among Indonesian EFL learners. Over eight weeks, the research involved 30 high-beginner EFL learners, employing vocabulary tests, speaking tests, and a survey for data collection. The analysis utilized paired t-tests for the test results and descriptive analysis for the survey findings. The results demonstrated notable improvements in both vocabulary and speaking skills, with a t-value of -13.772 for vocabulary and a z-value of -4.816 for speaking, confirming that Speak Up® effectively enhanced learners' abilities. Additionally, a positive correlation was identified between vocabulary acquisition and speaking fluency, with an effect size of 0.85, indicating a substantial impact. Survey results reflected favorable perceptions of Speak Up®, with mean scores of 4.56 for effectiveness, 4.59 for usability, and 4.62 for satisfaction. Based on these findings, it is recommended that EFL teachers incorporate Speak Up® into their teaching strategies to improve vocabulary and speaking skills. Future research could investigate the long-term effects of Speak Up® on vocabulary retention and explore its benefits for improving speaking skills with a larger, more diverse sample, while also considering external factors that may influence vocabulary development and speaking skills.